Analisis Pengaruh Pengetahuan Perpajakan, Pelayanan Fiskus Dan Sanksi Denda Terhadap Kepatuhan Wajib Pajak Dalam Membayar Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan Di Kota Pasuruan - Fita Fitrianingsih; S. Sudarno; Taufik Kurrohman (UPT Penerbitan Universitas Jember, 2018)
This study aimed to examine the effect of taxation knowledge, government services, and sanctions fines against compliance taxpayers in paying property tax rural and urban in pasuruan city. This study uses primary data obtained from the questionnaires data distributed to respondents property taxpayer into the sample. Method of data analysis is multiple linear regression with program data processing uses SPSS version 23. The results showed that the taxation knowledge partially no effect on compliance taxpyers, while government service and sanctions fines partially positive effect on compliance taxpayer in paying property tax in rural and urban. Taxation knowledge, government services and sanctions fines simultaneously or together positive effect on compliance taxpayers. Keywords: compliance taxpayers, taxation knowledge, government services, and sanctions fines